Effectiveness of postpartum homecare program as a new method on mothers' knowledge about the health of the mother and the infant - Fatemeh Mokhtari; Parvin Bahadoran; Zahra Baghersad (Wolters Kluwer Medknow Publications, 2018)
Background: Reduced maternal mortality due to pregnancy and delivery is one of the priorities of reproductive health programs of World Health Organization. Benefiting from appropriate social support, such as receiving homecare, has an important role in mothers' adaptation and health. Lack of access to comprehensive and desirable health services is the most important barrier to improvement of maternal health. In this study, the effect of postpartum homecare on mother's knowledge about maternal and child health is evaluated. Materials and Methods: This study was two-group field trial which was conducted in 2015 on 62 postpartum mothers who were selected randomly in Shahid Beheshti Hospital of Isfahan. Mothers and infants of the intervention (experimental) groups were first visited at the hospital and then received two visits at home. The control group received routine postpartum care. A researcher-designed questionnaire was used for data collection. Data analysis was conducted using SPSS18 and independent, paired t-test, and Chi-square tests. Results: Comparing the demographic characteristics between both groups revealed no significant difference. After the intervention mothers' knowledge about maternal (t = 4.26; p < 0.001) and child (t = 3.19; p = 0.003) health showed a significant difference between the intervention (experimental) and control groups. Conclusions: Performance of postpartum homecare as a new and useful method in the health system of Iran can increase mothers' knowledge about their own health and their children, enhance their ability to adapt with the postpartum period, and improve the health level of vulnerable populations.